Further insights into the role of bHLH121 in the regulation of iron homeostasis in Arabidopsis thaliana. (2nd October 2020) - Gao, Fei; Robe, Kevin; Dubos, Christian
ABSTRACT: Iron (Fe) is an important micronutrient for plant growth and development but any excess of Fe is toxic because of the Fe-dependent generation of reactive oxygen species (ROS). Thus, Fe homeostasis must be tightly regulated. In Arabidopsis thaliana, a cascade of transcription factors has been identified as involved in the regulation of this process by modulating the expression of genes related to Fe uptake, transport, and storage. Recently, it was demonstrated that in response to Fe deficiency, bHLH121/URI (UPSTREAM REGULATOR OF IRT1) directly activates the expression of several genes involved in this regulatory network. It was also shown that bHLH121 interacts with ILR3 (bHLH105) and its homologs. Herein it is shown that bHLH121 is necessary for the expression of the main markers of the plant responses to Fe excess, the ferritin genes ( i.e. FER1, FER3, and FER4 ). bHLH121 regulates ferritin genes expression by directly binding to their promoters, at the same locus than the ILR3-PYE repressive complex. Therefore, this study highlight that bHLH121, PYE, and ILR3 form a chain of antagonistic switches that regulate the expression of ferritin genes. The implication of this finding is discussed.